Adaptive evolution of SARS-CoV-2 during a persistent infection for 521 days in an immunocompromised patient - Hanno Schmidt; Lea Schick; Jürgen Podlech; Angélique Renzaho; Bettina Lieb; Stefan Diederich; Thomas Hankeln; Bodo Plachter; Oliver Kriege (npj Genomic Medicine)
Abstract Immunocompromised patients struggle to adequately clear viral infections, offering the virus the opportunity to adapt to the immune system in the host. Here we present a case study of a patient undergoing allogeneic hematopoietic stem cell transplantation with a 521-day follow-up of a SARS-CoV-2 infection with the BF.7.21 variant. Virus samples from five time points were submitted to whole genome sequencing. Between the first detection of SARS-CoV-2 infection and its clearance, the patient’s virus population acquired 34 amino acid substitutions and 8 deletions in coding regions. With 11 amino acid substitutions in the receptor binding domain of the virus’ spike protein, substitutions were 15 times more abundant than expected for a random distribution in this highly functional region. Amongst them were the substitutions S:K417T, S:N440S, S:K444R, S:V445A, S:G446N, S:L452Q, S:N460K, and S:E484V at positions that are notorious for their resistance-mediating effects. The substitution patterns found indicate ongoing adaptive evolution.